STUDI KOMPARATIF TINGKAT PENDAPATAN PELAKU BISNIS YANG MENGGUNAKAN STRATEGI PEMASARAN OFFLINE DAN ONLINE (Studi Pada Pelaku Bisnis Thrifting Di Pasar Utan) - Asmini, A; Ismawati, I; Hendrawan, Ade (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to compare income levels between thrifting business actors at Utan Market who use offline and online marketing strategies. The type of this study was comparative study, and the type of data used was quantitative obtained directly from informants using interview guidelines. The informants in this study were 30 thrifting business actors at Utan Market, consisting of 15 thrifting business actors who used offline marketing strategies and 15 thrifting business actors who used online marketing strategies. The data analysis technique in this study was carried out using the Shapiro-Wilk normality test technique, paired samples statistics test, paired samples correlations test, and paired samples t-test. The results of this study showed that there was a significant difference in income levels between thrifting business actors at Utan Market who use offline and online marketing strategies. The income level of thrifting business actors at Utan Market who used online marketing strategies was higher than the income level of thrifting business actors who used offline marketing strategies. Thus, it can be stated that the implementation of online marketing strategies was a very important aspect in increasing the income of thrifting business actors at Utan Market. Through the implementation of online marketing strategies, it can make it easier for thrifting business actors to reach a wider market share. Thrifting business actors can offer their products to consumers more widely without being limited by place and time, thereby increasing sales activity which has an impact on increasing the income of thrifting business actors.